Crustal structure of Bohai Sea and adjacent area (North China) from two onshore–offshore wide-angle seismic survey lines. (February 2015) - Liu, Lihua; Hao, Tianyao; Lü, Chuanchuan; You, Qingyu; Pan, Jun; Wang, Fuyun; Xu, Ya; Zhao, Chunlei; Zhang, Jianshi
Highlights: We modeled two onshore–offshore survey lines with OBS in the shallow water. The deficiency of deep structure information of NCC in the sea area was made up. We tried to use the CMP stacking method to process the OBS data. We discussed the layers and east boundary of NCC destruction. Abstract: In 2010 and 2011 onshore–offshore surveys along two lines in the Bohai area were carried out. This paper presents the deep structure from wide-angle seismic data along the two lines, and try to improve the reliability of deep interfaces by using of the CMP prospecting method. The result is as follows. (1) The environmental noise of records from OBSs in shallow water area is stronger than that from deep waters. (2) The CMP stacking method is potential for high-density OBS surveys. (3) The thickness of sedimentary layer in Bohai Sea and surrounding area is 3–5 km, the velocity increases with depth from about 2 km/s at the seafloor to about 4.5 km/s on the sedimentary basement. (4) The upper crust thins toward the sea area from the land area, the middle and lower crust also vary insignificantly; the middle crust is about 4 km and the lower crust is about 15 km; the velocities of the middle and lower crust shows gentle variation in vertical but obvious in lateral due to the impact of fault zones. (5) The velocity contours nearby the Tancheng–Lujiang (TLFZ) and Zhangjiakou–Penglai (ZPFZ) Fault Zones are U-shaped, where the velocity changes laterally and the interface undulates significantly; velocity disturbances exist in the crust–mantle transition zone at the fault zones; the TLFZ and ZPFZ could be the upwelling channels of deep material. (6) In the eastern part of North China Craton (NCC), the Moho gently ranges at the depth of about 30 km with local rises; lithosphere thinning occurred predominantly at the top of upper mantle; the east boundary of lithosphere thinning is inferred to be on the east of Bohai Sea.